Bioinformatics analysis and experimental validation of ferroptosis genes in heart failure and atrial fibrillation - Wang, Zhi; Yuan, Chi; Xu, Tao; Xie, Weixing; Wu, Jiehua; Wang, Hegui (Frontiers in Genetics, 2025)
Background and objectivesAtrial fibrillation (AF) and heart failure (HF) are common cardiovascular diseases associated with significant morbidity and mortality in patients with both conditions. The objective of this research is to enhance our understanding of the shared pathogenesis underlying the two diseases and to identify novel therapeutic targets.Materials and methodsDifferentially expressed genes (DEGs) in heart failure and atrial fibrillation were obtained through the analysis and comparison of transcriptional expression profiles from the Gene Expression Omnibus (GEO) datasets. By integrating these datasets with the known ferroptosis-related genes (FRGs) from GeneCards and PubMed, we identified ferroptosis-related differentially expressed genes (FRDEGs). Functional enrichment and the construction of the PPI network for key genes were conducted. The mRNA-miRNA and mRNA-TF Regulatory Network were constructed via the ChIPBase and TarBase databases. Receiver operating characteristic (ROC) was utilized to screen out the FRDEGs and validate their diagnostic values. Gene expression levels were detected by qPCR in patient serum samples.ResultsBy analyzing the transcriptional expression profiles of the GEO datasets, TFRC, CP, SAT1, STEAP3, AKR1C1 and LPCAT3 were identified as FRDEGs in AF and HF, which were revealed to be involved in iron ion transport, homeostasis, and oxidoreductase activity. Further insights from Gene Set Enrichment Analysis (GSEA) indicated that FRDEGs are primarily enriched in the IL-12 signaling pathway in HF and significantly enriched in the collagen assembly pathway in AF. The diagnostic efficacy of six genes in AF validation sets was good (AUC:TFRC 0.940, CP 0.920, SAT1 1.000, STEAP3 0.960, AKR1C1 0.900, LPCAT3 0.960, as well as in the HF validation set (AUC: TFRC 0.842, CP 0.879, SAT1 0.865, STEAP3 0.787, AKR1C1 0.812, LPCAT3 0.696).Utilizing the GOSemSim package, we conducted a functional similarity analysis on the five hub genes and discovered their significant roles in disease, ranked as follows: STEAP3>TFRC>CP>SAT1>LPCAT3. qRT-PCR verified the expression differences of CP, STEAP3, and LPCAT3.ConclusionOur findings provide a theoretical basis for the clinical diagnosis and treatment of AF and HF. These results provide valuable insights into potential biomarkers for diagnosis and targets for therapeutic intervention in AF and HF.